On Rumors and Their Debunking: Howto Deal with Misinformation? - Petrova, Daria (Journal of Economic Sociology, 2024)
“Political Rumors: Why We Accept Misinformation and How to Fight It” is the result of Adam Berinsky’s long-term research, which analyses different aspects of rumors as a form of inaccurate information. It examines how rumors spread and persist in media space due to their virality, repetition and social transmission. Factors related to the belief in misinformation are highlighted, among them the tendency to conspiracy thinking and dogmatism, as well as political non-involvement. Combining psychological and political science approaches, the author focuses on the peculiarities of perception of rumors and their refutations. Although the effect is short-term, a productive strategy is to correct rumors that resonate with an individual’s political orientation. Through a series of experiments, the book proves the propensity of people to confirm their beliefs, whereby sources whose party identity matches the person’s perceptions have greater credibility. In contrast, in the case of refutations, information broadcast by sources that benefit from the rumor, respectively, come into opposition with one’s political attitudes and partisanship. The book offers a new way of considering the possibilities of unmasking rumors by employing psychological and heuristic mechanisms of information perception and shifting attention from neutral sources of debunking to those with distinct political biases.